2021
DOI: 10.1186/s12912-021-00742-9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the most important workplace factors in predicting nurse mental health using machine learning techniques

Abstract: Objectives Nurses are at a high risk of developing mental health problems due to exposure to work environment risk factors. Previous research in this area has only examined a few factors within nurses’ work environments, and those factors were not conceptualized with the goal of improving workplace mental health. The purpose of this study is to identify the most important work environment predictors of nurse mental health using a comprehensive and theoretically grounded measure based on the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…More specifically, patient dissatisfaction levels are high in workplaces with highly dissatisfied or burned-out nurses 35. This is further evidenced by previous research with the standard that consistently found workload management, psychological protection, engagement, and physical safety as important determinants of nurse anxiety, depression, PTSD, burnout, and life satisfaction 9. In light of these findings, future research should evaluate the mediating effect of nurse mental health on the relationship between GMW factors and quality and safe care provision.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…More specifically, patient dissatisfaction levels are high in workplaces with highly dissatisfied or burned-out nurses 35. This is further evidenced by previous research with the standard that consistently found workload management, psychological protection, engagement, and physical safety as important determinants of nurse anxiety, depression, PTSD, burnout, and life satisfaction 9. In light of these findings, future research should evaluate the mediating effect of nurse mental health on the relationship between GMW factors and quality and safe care provision.…”
Section: Discussionmentioning
confidence: 70%
“…The most concerning were psychological protection and the workload management conditions of nurses' work environments 2. Furthermore, another recent study of the Standard has found that among the 13 workplace factors, workload management, worklife balance, and psychological protection were the most important determinants of nurse adverse mental health outcomes including depression, anxiety, and posttraumatic stress disorder (PTSD) 9…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ISO provides a framework for identifying and addressing workplace risk factors to employee psychological health and safety across a wide range of industries and sectors including healthcare. In Canada, studies of the Canadian Standard identified workplace risk factors most predictive of nurses’ mental ill health and their quality and safety of care delivery [ 19 , 32 ]. Despite this progress, the implementation of ISO is yet to be mandated in healthcare by governments internationally.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this work identified 13 psychosocial risk factors that were integrated into the National Standard of Workplace Psychological Health and Safety (“the Standard”). The Standard and its measurement tool were recently validated among Canadian nurses [ 19 , 20 ]. According to these studies, ineffective workload management and lack of or limited psychological protection in the workplace were consistently among the strongest predictors of five mental health and three care delivery outcomes.…”
Section: Introductionmentioning
confidence: 99%